Monoclonal antibody binding to a surface exposed epitope on Cowdria ruminantium that is conserved among light strains - Shompole, S.; Rurangirwa, F.R.; Wambugu, J.; Sitienei, J.; Mwangi, David Miano; Musoke, A.J.; Mahan, S.; Wells, C.W.; McGuire, T.C. (2000)
Monoclonal antibodies (MAb) binding to Cowdria ruminantium elementary bodies (CB) were identified by enzyme-linked immunosorbent assay, and surface binding of one MAb (446.15) to intact CB was determined by immunofluorescence, immunogold labeling, and transmission electron microscopy. MAb 446.15 bound an antigen of approximately 43 kDa in immunoblots of eight geographically distinct strains. The NIAb did not react with Ehrlichia canis antigens or uninfected bovine endothelial cell lysate and may be useful in diagnostic assays and vaccine development.